Improved variable step-size LMS algorithm based on hyperbolic tangent function - Jianwu ZHANG; Hao YU; Qianhua ZHANG (Tongxin xuebao)
In order to improve that the LMS algorithm for determining step size cannot satisfy both rapid convergence and low steady-state misalignment errors,a variable step size algorithm (IVSSLMS) based on an improved hyperbolic tangent function was proposed.The step size feedback factor and the correlation value of the error signal were used to adjust the step size,and the problems of slow convergence speed and poor anti-noise ability of the fixed-step size algorithm was overcame.The performance and parameters settings of the proposed algorithm were analyzed.The simulation results show that IVSSLMS has a faster convergence rate,lower steady-state error and better system tracking capability than the existing variable step size algorithms under high and low SNR conditions.